The color of crime: racial hoaxes, white crime, media messages, police violence, and other race-based harms - Russell-Brown, Katheryn (Critical America, 2021)
Definitions, Statistics, and Issues -- Media Messages -- History's Strange Fruit -- Racial Discrimination, Racial Profiling, and Racial Monitoring -- Racial Hoaxes -- White Crime -- Race and Crime Literacy -- The Soul Savers.